Effectiveness of Developmental Program for District Core Teams in Mobilizing HIV/AIDS Prevention among Youth in Public Health Office Region 14 - ศิลป์ตระกูล, มยุรี; เทพหัสดิน ณ อยุธยา, ทิติยาณี (Disease Control Journal, 2011)
This study used a quasi-experimental design to evaluate the effectiveness of a capacity building program for district core teams in developing a task force on HIV/AIDS prevention among young people. The capacity building program was adapted from a sexuality education and learning design created by a global health group PATH and a guideline from Ottawa Charter for health promotion. The study subjects consisting of 30 community leaders from 6 districts of Public Health Office Region 14 were evaluated after 2-year intervention programs (from October 2008-September 2010). The program interventions were 1) providing a training course for core teams to improve their conceptual framework and work practices, 2) field visit for supporting and follow-up, 3) organizing a knowledge sharing forums and 4) setting an after action review at the end of the project. The results indicated statistical significant increases in knowledge and attitude of HIV/AIDS-related issues in the intervention group (p-value < 0.01). The effectiveness of capacity building program for district core teams on HIV/AIDS prevention was demonstrated. The qualitative evaluation revealed that 5 district core teams were able to create HIV/AIDS prevention task forces for youth in the areas by acting as a strategic manager and developed mechanisms such as a working group from all relevant sectors, using and analyzing useful information, developing integrative and effective plan which focusing on building capacity for community leaders who were responsible for youths, and convincing the local government to get involve in annual work plan and budgetary. Thus, capacity building for district core teams should be continuously implemented to improve systematic conceptual framework for developing HIV/AIDS prevention task force as well as to further adapt to be strengthened and sustainable districts on disease prevention and control according to the policy of the Department of Disease control.